2007
DOI: 10.1093/icesjms/fsm090
|View full text |Cite
|
Sign up to set email alerts
|

Spring diet of ringed seals (Phoca hispida) from northwestern Spitsbergen, Norway

Abstract: Labansen, A. L., Lydersen, C., Haug, T., and Kovacs, K. M. 2007. Spring diet of ringed seals (Phoca hispida) from northwestern Spitsbergen, Norway. – ICES Journal of Marine Science, 64: 1246–1256. Complete gastro-intestinal tracts (GITs) from 267 ringed seals from five different locations in Spitsbergen were collected during spring of the years 2002–2004. Diet was assessed based on hard part remains from prey. Invertebrates constituted <2% of all prey (relative frequency, Ni). Fish otoliths were found in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 27 publications
5
39
3
Order By: Relevance
“…obs.). The predation pressure on amphipods by fish and seals (Labansen et al 2007) remains unknown in our study area.…”
Section: Seasonality In the Trap Catchesmentioning
confidence: 92%
“…obs.). The predation pressure on amphipods by fish and seals (Labansen et al 2007) remains unknown in our study area.…”
Section: Seasonality In the Trap Catchesmentioning
confidence: 92%
“…and capelin Mallotus villosus, with diet varying by age, space (e.g. Lowry et al 1980, Labansen et al 2007, Yurkowski et al 2016a) and season (e.g. Siegstad et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The life history of ringed seals has been strongly shaped by sea ice dynamics (Smith and Hammill 1981), as stable land-fast ice is their preferred breeding habitat over pack ice (Smith and Stirling 1975). Ringed seals are trophic omnivorous consumers (Weslawski et al 1994;Dehn et al 2007;Labansen et al 2007;Thiemann et al 2007) that have been reported to undergo an ontogenetic shift in diet from invertebrates to fish (Bradstreet and Cross 1982;Holst et al 2001;Young et al 2010). Ringed seals consume a wide variety of prey species, from herbivorous and carnivorous invertebrates such as mysid, euphausiid, amphipod, and decapod species to fish such as Arctic cod (Boreogadus saida), capelin (Mallotus villosus), sand lance (Ammodytes sp.…”
Section: Introductionmentioning
confidence: 99%